Kontra Narasi atas Tanggapan Ibnu Rusyd terhadap Imam Al-Ghazali Terkait Apostesi Filosof - Adib, Ahmad Hidhir; Dliyauddin, Ahmad; Nisa', Luthfi Karimatun; Afida, Narse Nur (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
The dialogue between Imam Al-Ghazali and Ibn Rushd is one of the most monumental stories in the study of Islamic philosophy, in which his criticism of Al-Ghazali is refuted by Ibn Rushd with his various arguments. The purpose of this article is to strengthen Imam Al-Ghazali's criticism of the philosophical eschatological paradigm. The research method used is descriptive qualitative. The results of this study indicate that (1) Imam Al-Ghazali sentenced the philosophers to be disbelievers who held this view of nature as eternality, God does not know the details, and the resurrection of the soul on the Day of Judgment. (2) However, this verdict was criticized by Ibn Rushd. That nature is eternal, because its existence coincides with the beginning of time. Then this knowledge of God has nothing to do with a detailed or global model of knowledge, because God is the substance that causes an object to exist. Then this religious text is metaphorical in nature, so it is not certain that it is the body that is resurrected. (3) It's just that, the majority of scholars' from Sunni circles support Imam Al-Ghazali's statement. They based it on religious texts QS. Al-Hadid verse 3 about the eternality of nature, QS Al-An'am verse 28 regarding the knowledge of God, and QS Al-Kahf verse 47 and Al-Anbiya '104 regarding the resurrection of the body.